2015
DOI: 10.3109/15513815.2015.1051252
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal purulent meningitis in southern Tunisia: Epidemiology, bacteriology, risk factors and prognosis

Abstract: This study emphasizes the severity of PNM with high rates of mortality and neurological sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The number of pathogen species described in the included articles varied from 8 to 19. The two main etiologic agents were found to be Group B Streptococcus (GBS) and Escherichia coli in 4 studies [not including ( 9 , 14 , 19 )]. No ANOVA analyses were performed in these articles to determine the exact statistical relationship between these pathogens and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The number of pathogen species described in the included articles varied from 8 to 19. The two main etiologic agents were found to be Group B Streptococcus (GBS) and Escherichia coli in 4 studies [not including ( 9 , 14 , 19 )]. No ANOVA analyses were performed in these articles to determine the exact statistical relationship between these pathogens and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies of the 72 had a sample size <50 and were included because large studies were not available for those countries: Bosnia and Herzegovina, [ 30 ] Nepal, [ 31 ] Nigeria, [ 32 ] Romania, [ 33 ] and Tunisia. [ 34 ] The methodological quality assessment of each of the included studies is shown in S3 Table . Approximately 90% of these studies were cross-sectional studies (n = 49/72) or surveillance studies (n = 14/72).…”
Section: Resultsmentioning
confidence: 99%
“…[ 83 ] An additional analysis was carried out in our study for data in neonates on the frequency of group B S . agalactiae for all regions and found that the frequency was highest in the European region (but limited to one study only [ 84 ]), and lowest in the Eastern Mediterranean region (based on two studies only [ 34 , 85 ]). It has been estimated that group B S .…”
Section: Resultsmentioning
confidence: 99%
“…As a result of these findings, together with MRI examination, the patient was diagnosed with GA II complicated purulent meningitis and septicemia. Purulent or bacterial meningitis is characterized by the invasion and growth of bacteria in the CSF, which is more frequent during the neonatal period than at any other period of life [22]. The clinical features of neonatal bacterial meningitis are nonspecific, CSF study through lumbar puncture is the only way to confirm the diagnosis of meningitis and we examined this case.…”
Section: Discussionmentioning
confidence: 99%